Giono, Translator or Reader of Moby-Dick? - Génin, Isabelle (TTR, 2014)
The article discusses the interaction between reading and translating, in the case of the first unabridged translation of Moby-Dick into French by Jean Giono, Lucien Jacques and Joan Smith, published by Gallimard in 1941. After a brief survey of the status of that translation—an important cultural landmark in France—the paper examines what the paratext (Giono’s diary, notes and letters) and the typescripts reveal about a seemingly paradoxical situation: Giono’s keen reading of Moby-Dick on the one hand and the simplification and clarification strategies adopted in the translation on the other hand. A selection of stylistic analyses illustrates both the choices made by the translators and the part played by each participant in the project. It appears that Giono did not necessarily misread Moby-Dick, underestimating its scope and significance. Instead, after reading the novel, he grew indifferent to its translation and concentrated his energy on his own writing in which he re-invested his reading experience. As to the other co-translators, Joan Smith provided a word-for-word translation of the text that made no attempt at interpreting the text, while Lucien Jacques strove to re-write Smith’s literal first draft, in spite of his difficult position as a non-reader (albeit an enthusiastic one) of Moby-Dick.